A Yuletide kiss - Hunter, Madeline; Jeffries, Sabrina; Putney, Mary Jo (Kensington Books, 2021)
The unexpected gift: Jenna Waverly has closed her inn, anticipating a blissfully quiet Christmas, until a snowstorm brings the first of several strangers to her property. Lucas Avonwood, as charming as he is secretive, is on a mission to track down a scoundrel, but the inn's lovely owner is giving him a more compelling reason to stay.